The EU succession regulation : a commentary / edited by Alfonso Luis Calvo Caravaca, Universidad Carlos III de Madrid, Angelo Davi, Universita di Roma "La Sapienza", Heinz-Peter Mansel, Universitat zu Koln. - Calvo Caravaca, Alfonso-Luis; Davì, Angelo; Mansel, Heinz-Peter (Cambridge University Press, 2016)
The European Succession Regulation is a landmark in the field of EU private international law. It unifies the conflicts of laws, jurisdiction and recognition of foreign judgments and some other legal instruments in the field of succession and wills. This volume provides an article-by-article commentary on the individual provisions of the Regulation, introduced by an overview of its general framework and underlying principles. As a reference tool for the Regulation, this book is intended to promote a high standard of interpretation and application. With contributions from leading scholars in the field, it uses a comparative approach in its analysis to enrich the academic debate and highlight the problems likely to arise in the practical application of the Regulation.